PENGARUH KUALITAS PRODUK, BRAND IMAGE, DAN PENGGUNAAN JASA ENDORSEMENT TERHADAP KEPUTUSAN PEMBELIAN PERHIASAN PERAK DI SUNAKA JEWELRY CELUK, SUKAWATI, GIANYAR - Rumaladewi, Ni Kadek Bintang Indah; Taun, I Nyoman (Universitas Pendidikan Nasional, 2019)
This study aims to determine: (1) the effect of product quality on purchase decision of silver jewelry in Sunaka Jewelry, (2) the effect of brand image on purchase decision of silver jewelry in Sunaka Jewelry, (3) the effect of endorsement usage on purchase decision of silver jewelry in Sunaka Jewelry, and (4) the effect of product quality, brand image, and endorsement usage on purchase decision of silver jewelry in Sunaka Jewelry. This research is a survey research. Population in this research is all customer of Sunaka Jewelry Celuk, Sukawati, Gianyar which purchased silver jewelry from Sunaka Jewelry. The sampling technique used accidental sampling with the number of samples counted 75 peoples. Data collection technique using questionnaires that have been tested for validity and reliability. Data nalysis technique used is multiple regression.The results of the research shows that: (1) product quality had positive effect on purchase decision on Sunaka Jewelry (showed by the significance value of 0,006 < 0,050 and regression coefficient = 0,206), (2) brand image had positive effect on purchase decision on Sunaka Jewelry (showed by the significance value of 0,028 < 0,050 and regression coefficient = 0,250), (3) endorsement usage had positive effect on purchase decision on Sunaka Jewelry (showed by the significance value of 0,015 < 0,050 and regression coefficient = 0,231), and (4) the product quality, brand image, and endorsement usage influence simultaneaously to purchase decision on Sunaka Jewelry (showed by F count = 23,753 and significance value of 0,000 < 0,050).Keywords: product quality, brand image, endorsement usage, purchase decision